Gelidiophycus (Rhodophyta: Gelidiales): A new genus of marine algae from East Asia. Issue 6 (1st December 2013) - Boo, Ga Hun; Park, Jeong Kwang; Boo, Sung Min
Abstract: A new genus of gelidioid red algae, Gelidiophycus, is described. Separated from Gelidium on the basis of a molecular phylogeny and morphological characters, it contains two species, Gelidiophycus freshwateri sp. nov. and G. divaricatus comb. nov., distributed in East Asia. Our rbcL and cox1 phylogenies revealed close relationships of Gelidiophycus with the Capreolia group in Australasia and unidentified taxa in Chile. Gelidiophycus is characterized by repent thalli and lateral branches arising at almost right angles. The occurrence of tetrasporophytes, male and female gametophytes, and carposporophytes in the field indicate that both species have the triphasic type life history, different from Capreolia. Gelidiophycus freshwateri occurs in Korea, China, and Japan, and G. divaricatus is found in Hong Kong. We discuss Gelidiophycus and its two species and provide keys, descriptions, and illustrations.